Exploiting the Common Data Structure Linking Patient Record and Knowledge Base in the FRAMEMED System - Bishop, Charles W. (1993)
The purpose of this poster is to show that the format of records of patient encounters in the Chronological Medical Record (CMR) (part 3 of our proposed 4-part patient medical record) are essentially the same as the format of the of the Relational Records in the FRAMEMED knowledge base (FKB). Because the same coded phraseology is used in both types of records and because the items in any record are in code order, any series of records (presently up to 5) can be interdigitated for easy comparison.